Exercise with the intensity of the individual anaerobic threshold in acute hypoxia - Friedmann, B.; Bauer, T.; Menold, E.; Bärtsch, P. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The aim of the present study was to find out if the determination of the individual anaerobic threshold (IAT) during incremental treadmill tests in normoxia and acute normobaric hypoxia (FiO2 0.15) defines equivalent relative submaximal intensities in these environmental conditions. Methods: 11 male middle and long distance runners performed a 1-h treadmill run in normoxia and hypoxia at the intensity of the IAT determined in the respective environment with measurement of lactate, glucose, heart rate, catecholamines, ventilatory parameters, and rate of perceived exertion (RPE). Results: During the 1-h treadmill runs, speed was significantly reduced in hypoxia compared with normoxia (12.8 +/- 0.7 vs 14.7 +/- 0.7 km [middle dot] h-1). Relative intensity expressed as a percentage of [latin capital V with dot above]O2max was similar in both environments (82-83% on the average) and elicited comparable lactate steady states [LaSS, 2.5 +/- 0.7 - 3.4 +/- 1.1 mmol [middle dot] L-1 (normoxia), 2.7 +/- 0.8 - 3.6 +/- 1.0 mmol [middle dot] L-1 (hypoxia) after 10 and 60 min, respectively] and glucose levels, but significantly reduced heart rate in hypoxia by 5 beats [middle dot] min-1 on the average. A steady state was also found for the ventilatory parameters. Plasma epinephrine and norepinephrine levels were similar in both environments. RPE was significantly lower after 40-60 min of exercise in hypoxia. Conclusions: Relative intensities in normoxia and acute hypoxia are equivalent when endurance exercise is performed with the running speed at the IAT determined in the respective environment. The heart rate-blood lactate relationship, however, is changed in hypoxia and relative submaximal exercise intensity is higher in acute hypoxia when training is performed with similar heart rate as in normoxia.